Spontaneous Reports of Serious Adverse Drug Reactions Resulting From Drug–Drug Interactions: An Analysis From the French Pharmacovigilance Database - Létinier, Louis; Ferreira, Amandine; Marceron, Alexandre; Babin, Marina; Micallef, Joëlle; Miremont-Salamé, Ghada; Pariente, Antoine; , on behalf of the French Network of Pharmacovigilance Centres (Frontiers in Pharmacology, 2021)
Few data are available on the clinical impact of Drug-Drug Interactions (DDIs). Most of the studies are limited to the analysis of exposure to potential DDI or to the targeted impact of the combination of a few drugs or therapeutic class. The analysis of adverse drugs reactions reports could be a mean to study generally the adverse effects identified as due to a DDI. Our objective was to describe the characteristics of adverse drugs reactions (ADRs) resulting from DDIs reported to the French pharmacovigilance system, and to identify the drugs most often implicated in these. Considering all ADR reports reported from 01/01/2012 to 31/12/2016, we identified all cases of ADR informed as resulting from a DDI (DDI-ADRs). We then described these in terms of patients’ characteristics, ADR seriousness, drugs involved (two or more per case), and ADR type. Of the 4,027 reports relating to a DDI-ADRs, 3,303 were related to serious ADRs. Patients with serious DDI-ADRs had a median age of 76 years (Inter-Quartile Range: 63-84); 53% were male. Of all serious DDI-ADRs 11% were life-threatening and 8% fatal. In 36% of cases, the DDI causing the ADR involved at least three drugs. Overall, 8,424 drugs different drugs were mentioned in the 3,303 serious DDI-ADRs considered. Altogether, drugs from the “Antithrombotic agents” subgroup were incriminated in 34% of serious DDI-ADRs. Antidepressants was the second most represented therapeutic/pharmacological subgroup (5% of serious DDI-ADRs). Across the 3,843 ADR types reported in the 3,303 serious DDI-ADRs considered, the most frequently represented were hemorrhage (40% clinical hemorrhage; plus biological hemorrhage, 6%), renal failure (8%), pharmacokinetic alteration (5%) and cardiac arrhythmias (4%). Hemorrhagic accidents still accounted for an important part of serious ADRs resulting from DDIs reported in France. The other clinical consequences of DDIs seem less well identified by pharmacovigilance. Moreover, more than one third of serious DDI-ADRs involved at least three drugs.